Challenges and Opportunities in the Renewable Energy Transition in Europe - Alina-Oana Chiva (Journal of Research and Innovation for Sustainable Society)
The transition to renewable energy is pivotal for the European Union (EU) in its efforts to combat climate change and reduce reliance on fossil fuels. This article examines the challenges and opportunities associated with the EU's target of achieving at least 42.5% renewable energy consumption by 2030. Utilizing a comparative analysis of EU member states, it is assessed the renewable energy shares, achievements, and gaps. The methodology employed in this research is a mixed-method approach combining quantitative and qualitative analyses to evaluate the progress of renewable energy adoption in the EU and the barriers to achieving the 2030 targets. The analysis highlights the role of targeted policy interventions and increased investment in accelerating renewable energy deployment. Ultimately, this study underscores the need for cohesive strategies to enhance the resilience and sustainability of the EU’s energy system as it strives to meet its climate objectives